2022
DOI: 10.1002/ldr.4445
|View full text |Cite
|
Sign up to set email alerts
|

Estimating soil salinity under sunflower cover in the Hetao Irrigation District based on unmanned aerial vehicle remote sensing

Abstract: Soil salinization is one of the important factors limiting the sustainable development of agriculture and causing land degradation. In order to explore the effect of growth stage division on the estimation accuracy of soil salt content (SSC) in fields cropped with sunflower, multiple time-series unmanned aerial vehicle (UAV) were used to monitor SSC in the Hetao Irrigation District, Inner Mongolia, China. Aerial and field campaigns for four growth stages of sunflowers in six study areas were conducted from Jul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 47 publications
(61 reference statements)
0
1
0
Order By: Relevance
“…Similar to the present study, the wasteland in the study area continued to accumulate salts under salt recharge from groundwater, and salt accumulation reached a maximum by the end of the reproductive period. Cui et al [38] analyzed the relationship between soil salinity and groundwater in the Yao Ba Oasis and found a significant correlation between surface soil salt fractions, salt content, and groundwater. Wang et al [39] indicated that groundwater depth and salinity are the main factors affecting soil salinization in river oases.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to the present study, the wasteland in the study area continued to accumulate salts under salt recharge from groundwater, and salt accumulation reached a maximum by the end of the reproductive period. Cui et al [38] analyzed the relationship between soil salinity and groundwater in the Yao Ba Oasis and found a significant correlation between surface soil salt fractions, salt content, and groundwater. Wang et al [39] indicated that groundwater depth and salinity are the main factors affecting soil salinization in river oases.…”
Section: Discussionmentioning
confidence: 99%
“…Using optical remote sensing to determine the crop growth status and indirectly inverting soil salt content (SSC) is still a commonly used monitoring method. It mainly establishes a certain relationship among the reflectance, spectral index, and SSC and then estimates soil salt in the crop root zone [44,45]. However, the optical remote sensing information is complex, and if the redundant spectral information is not screened, the stability and accuracy of the monitoring model will be affected [46].…”
Section: Comparison Of Variable Filtering Methodsmentioning
confidence: 99%
“…Hence, two natural indicators, including temperature and precipitation, and four human indicators, including total power of agricultural machinery, total output value of the plantation industry, production of raw coal, and population, were selected to explore the driving factors behind oasis transitions. Pearson's correlation coefficient (r) was used to express the linear correlation between two variables [41]. In this study, we quantified the driving forces between driving factors and oasis changes using the r-value.…”
Section: Driving Forces For Oasis Transitionmentioning
confidence: 99%